Hemoptysis and Endometriosis: An Unusual Association — Case Report and Review of the Literature - Leonardo-Pinto, Joao Paulo; Benetti-Pinto, Cristina Laguna; Quagliato, Iuri; Yela, Daniela Angerame (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Thoracic endometriosis syndrome is a rare condition that includes four entities: catamenial pneumothorax, catamenial hemothorax, catamenial hemoptysis and lung nodules. We describe the case of a 23-year-old woman with complaints of hemoptysis during menstrual period in the two years prior to the appointment. Initially, a treatment for tuberculosis was established with no success. Further investigation showed a 4 mm nodule in the right lung, and the transvaginal ultrasonography indicated the presence of deep endometriosis. Considering the occurrence of symptoms only during menses, an empirical therapy was instituted with remission of the complaints.
Keywords: endometriosis; hemoptysis; thoracic endometriosis syndrome